2008
DOI: 10.1089/end.2008.0346
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Treatment Outcome of a New Electromagnetic Lithotripter for Upper Urinary Tract Calculi

Abstract: Outpatient based electromagnetic SWL using the Lithoskop achieves high fragmentation and success rates with minimal analgesia requirements and a low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
4
9
1
Order By: Relevance
“…We evaluated success after only one treatment session. By contrast, other authors have regarded SWL treatment as successful, when patients were free of stones within three sessions [17,26]. Therefore, the overall therapy success in the present series was only 53.1%.…”
Section: Discussioncontrasting
confidence: 63%
“…We evaluated success after only one treatment session. By contrast, other authors have regarded SWL treatment as successful, when patients were free of stones within three sessions [17,26]. Therefore, the overall therapy success in the present series was only 53.1%.…”
Section: Discussioncontrasting
confidence: 63%
“…With increased size, the number of sessions, shocks and also the rate of voltage were increased while the post procedure stone–free rate decreased. Other authors report similar findings such as Seitz et al, 2008 [15]. Abdelghany et al, 2011 [5] reported a significantly higher stone–free rate when stone size was <8 mm.…”
Section: Discussionsupporting
confidence: 58%
“…However, Seitz et al, 2008 [15] reported that only the maximum diameter of the stone affected the ESWL success. The authors of this study emphasized that these findings are in accordance with the AUA recommendations that ESWL can be used for the management of distal ureteric stones of 11 to 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The energy setting (cumulated total energy dose of ~90 J) used for this study was at an intermediate level of clinical SWL. 29 At high energy and PRF, the enhancement of cavitation activity may increase the propensity of renal injury from rupture of small vessels during bubble expansion. 30 Additional studies at higher energy settings and PRFs >1 Hz will be needed to define the safety limit of acoustic pulse energy and total dose applicable to the treatment of kidney and ureteral stones.…”
Section: Discussionmentioning
confidence: 99%